STUDI KERJA PROTEKSI RELAI OCR DAN GFR PADA PENYULANG ULUWATU SETELAH REKONFIGURASI - Galih Budi Santosa; I Gede Dyana Arjana; I Wayan Arta Wijaya (Jurnal SPEKTRUM, 2021)
PT. PLN (Persero) South Bali Area built the Pecatu GIS to level the load, improve serviceand reliability of the electricity distribution system. The transfer of electrical loads to the PecatuGIS changes the configuration of the Pecatu feeder to the Uluwatu feeder and the Labuan Saitfeeder. Changes in load current and network impedance have an impact on short-circuit faultcurrents. The calculation of short-circuit fault current becomes the basis for determining theworking time of the OCR and GFR relays between the recloser and the feeder base PMT. Therelay working time based of the PLN regulation setting protection at 0,1 seconds to eliminatefault currents and IEC 60255 standard take 0,3 seconds to eliminate fault currents. The resultsof the study showed that the time value of PLN's regulation Tms was 0,076 SI and 0,033 SI.The results of the calculation of (Tms) standard IEC 60255 obtained time (Tms) 0,23 SI and0,09 SI. The simulation results of the PLN regulation relay settings and IEC 60255 work wellwith a grading time value of 0,2 – 0,4 seconds.